1992
DOI: 10.1017/s003118200006176x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of peptidases inTrypanosoma cruziepimastigotes using chromogenic and fluorogenic substrates

Abstract: SUMMARYDetergent extracts of Trypanosoma cruzi epimastigotes catalysed the hydrolysis of a range of amino-acyl and peptidyl />-nitro-anilides and aminomethylcoumarins. At least three enzymes were detected that cleave Z-Phe-Arg-MCA. Two of these were optimally active at alkaline pH, the other at pH 4-0. Of the two enzymes with alkaline pH optima, one was a cysteine peptidase and was unable to cleave Bz-Arg-MCA readily, whilst the other cleaved Bz-Arg-MCA and was inhibited by diisopropyl fluorophosphate. The aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Synthetic peptide substrates containing AMC, MNA or 3-amino-o-ethylcarbazole fluorescent groups have been used as highly sensitive and specific tools to study proteinases in several species of protozoa [40]. Some T. cruzi proteolytic activities have been studied using such substrates [18,39,41,42]. In the present work, we demonstrate that cell-free extracts of T. cruzi amastigote, trypomastigote and epimastigote forms readily cleave a collagenase fluorogenic substrate with an optimal pH of about 8n0.…”
Section: Discussionmentioning
confidence: 57%
“…Synthetic peptide substrates containing AMC, MNA or 3-amino-o-ethylcarbazole fluorescent groups have been used as highly sensitive and specific tools to study proteinases in several species of protozoa [40]. Some T. cruzi proteolytic activities have been studied using such substrates [18,39,41,42]. In the present work, we demonstrate that cell-free extracts of T. cruzi amastigote, trypomastigote and epimastigote forms readily cleave a collagenase fluorogenic substrate with an optimal pH of about 8n0.…”
Section: Discussionmentioning
confidence: 57%
“…The plate was incubated at 30°C and read intermittently. Under these assay conditions, it was confirmed that the protease activity was sensitive to 40 M trans-epoxysuccinyl-L-leucylamido-(4-guanidino)-butane (E64; results not shown) and therefore corresponded to the lysosomal cysteine proteinase cruzipain (29,30) and not the cytosolic alkaline protease that is insensitive to this inhibitor (31). The release of pnitrophenol or p-nitroaniline from substrates was measured using a Dynatech MR5000 reader at 410 -450 nm.…”
Section: )mentioning
confidence: 89%
“…Additionally, the cysteine protease cathepsin B, a serine carboxipeptidase, and, more recently, two cytosolic metallocarboxypeptidases, a serine oligopeptidase and two aspartyl proteases have been biochemically characterized [13-17]. In contrast, the study of aminopeptidases has been limited to the detection of such activity in cell extracts of T. cruzi epimastigotes [18]. …”
Section: Introductionmentioning
confidence: 99%